2021
DOI: 10.1111/1541-4337.12695
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic tools for viable but nonculturable pathogens in the food industry: Current status and future prospects

Abstract: Viable but nonculturable (VBNC) microorganisms have been recognized as pathogenic contaminants in foods and environments. The failure of VBNC cells to form the visible colonies hinders the ability to use conventional media for their detection. Efficient and rapid detection of pathogens in the VBNC state is a prerequisite to ensure the food safety and public health. Despite their nonculturability, VBNC cells have distinct characteristics, such as morphology, metabolism, chemical composition, and gene and protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 248 publications
(260 reference statements)
0
15
0
Order By: Relevance
“…VBNC was first reported by Xu et al [ 30 ], and this finding was subsequently confirmed by several independent studies, with VBNC now commonly recognized as a critical survival strategy for bacteria [ 31 ]. Furthermore, a number of studies have been carried out globally on VBNC [ 32 , 33 , 34 ], showing the importance of this state on the bacterial life cycle and the implications for the relationship of bacteria with other species, including their hosts. However, there are no reports of VBNC in C. diphtheriae , despite the fact that C. diphtheriae is recognized as a reemerging human pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…VBNC was first reported by Xu et al [ 30 ], and this finding was subsequently confirmed by several independent studies, with VBNC now commonly recognized as a critical survival strategy for bacteria [ 31 ]. Furthermore, a number of studies have been carried out globally on VBNC [ 32 , 33 , 34 ], showing the importance of this state on the bacterial life cycle and the implications for the relationship of bacteria with other species, including their hosts. However, there are no reports of VBNC in C. diphtheriae , despite the fact that C. diphtheriae is recognized as a reemerging human pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Resazurin is a stable redox indicator that is reduced to resorufin by metabolically active bacteria (O'Brien et al, 2000; Pettit et al, 2005). Similarly to the XTT assay, it can quantify both viable and VBNC bacteria (Gao et al, 2021) and its results correlate well with CFU counts (Jiang et al, 2011a; Pettit et al, 2005; Sandberg et al, 2009). It is a rapid, inexpensive and less time‐consuming method compared to the XTT assay (O'Brien et al, 2000; Peeters et al, 2008) and it has been used as an initial screening method to explore the effect of different irrigant concentrations on biofilm (Jiang et al, 2011a).…”
Section: Antimicrobial Effectmentioning
confidence: 99%
“…FISH can assist microscopic identification of bacteria and it also provides detailed information on the spatial organization of mixed microbial communities (Figure 5; Chávez de Paz et al, 2015; Lukic et al, 2020; Sunde et al, 2003). Furthermore, it is very sensitive and can detect microorganisms independent of their growth, although limited data are available concerning the detection of VBNC bacteria (Gao et al, 2021). However, it requires an extensive preparation of the specimens, only a limited number of probes are available and hybridization may not be equally efficient in all cases (Azeredo et al, 2017).…”
Section: Antimicrobial Effectmentioning
confidence: 99%
“…Among non-culture techniques, nucleic acid amplification testing such as PCR is a revolutionary technique that is based on the detection of pathogen-specific RNA or DNA sequences in the sample [ 18 , 55 ]. It offers the in vitro amplification of a small amount of DNA/RNA or other amplifiable natural or synthetic nucleic acids of pathogens (including VBNC microorganisms).…”
Section: Conventional Techniques For Pathogen Detectionmentioning
confidence: 99%
“…The identification of specific pathogens using detection assays is based on the direct detection of different components in the sample such as deoxyribonucleic acid (DNA), ribonucleic acid (RNA), specific proteins, antigens, and enzymes. In comparison to existing reviews [ 18 ], this review will discuss most of the available and emerging advanced options for pathogen detection (refer to Scheme 1 ). A comparative analysis of these techniques along with future perspectives is also provided here (refer to the Supplementary Materials ).…”
Section: Introductionmentioning
confidence: 99%